An Encrypted File Deduplication Scheme with Permission in Cloud Storage. (7th November 2018) - Deng, Zuojie; Tan, Xiaolan; Chen, Shuhong
Abstract : Encrypted file deduplication scheme (EFD) can improve its storage space utilization of cloud storage and protect the privacy of files in cloud storage. However, if an enterprise stores its files to cloud storage that has deployed an encrypted file deduplication scheme that does not support permission checking, this will destroy the permission of the enterprise files and bring some security problems. This seriously affects the practical value of EFD and prevents it from deploying in concrete cloud storage. To resolve this problem, we propose an encrypted file deduplication scheme with permission (EFDSP) and construct the EFDSP by using the hidden vector encryption (HVE). We have analyzed the security of EFDSP. The results have shown that EFDSP is secure and it can prevent the online deduplication oracle attack. We implement EFDSP and conduct the performance evaluation. The results show that the performance of EFDSP is little inferior to that of SADS, which is the only existing encrypted file deduplication scheme with permission, but the performance gap decreases with the increasing number of the authorized users and EFDSP has overcome the security weakness of SADS.